Evaluación de la estrategia tecnológica para el control de la enfermedad de punta morada en dos variedades de papa (INIAP-CIP Libertad) y el (Clon 11991) en la Universidad Técnica de Cotopaxi, Campus Salache. - Vega Tigse, Ruth Maribel (2022)
The present investigation was in the Technical University of Cotopaxi - Salache Campus, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province. The general objective was to evaluate the technological strategy to control purple tip disease in two potato varieties (INIAP-CIP Libertad) and (Clone 11991). The specific object was to determine the agronomic behavior of the two potato varieties using the technological package, to identify the incidence of purple tip disease in two potato varieties, and to estimate the yield in two potato varieties. The following variables were evaluated: percentage of emergence, days to flowering, number of tubers per plant, the weight of tubers per plant, and population dynamics of Bactericera cockerelli. A descriptive analysis was applied, for which tables of averages and statistical graphs were made. From the results obtained, it was mentioned that the INIAP-CIP Libertad variety had a better agronomic performance compared to Clone 11991, the incidence of Bactericera cockerelli, Clone 11991 was inferior, and in terms of yield, INIAP-CIP Libertad was superior with 33 tons per hectare.